The effects of regular exercise on hippocampal estradiol levels and spatial memory of ovariectomized Sprague Dawley rats - Sri Kadarsih Soejono, Siti Kaidah Ginus Partadiredja (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2013)
The decrease of estrogen levels leads to dysfunction of hippocampus, including spatial learning and memory. Previous studies have shown that physical exercise improved spatial memory of ovariectomized rats. Physical exercise was observed to be associated with increased extragonadal aromatization and neurotrophin synthesis. This study aimed to evaluate the effect of regular exercise on serum and hippocampal estrogens levels and the spatial memory of ovariectomized rats. The present study used 10 ovariectomized Sprague Dawley rats aged 12 weeks. The rats were randomly assigned into two groups with five rats in each group. Group I was exercise group and Group II was control group without exercise. During the exercise period, the rats were required to keep running constantly on the treadmill at a speed of 18 m/min and at the slope of 5% for a total duration of 60 minutes per day. The exercise was performed five times per week for 12 weeks. The spatial memory of rats was measured using Morris water maze. After the exercise program was completed, the blood and hippocampus samples were collected to determine the estrogen levels. This study revealed that the mean levels of hippocampal estrogen of exercise group (33.794 ± 4.760 pg/mL/100mg tissue weight) were significantly higher than that ofcontrol group (20.552 ± 2.057 pg/mL/100 mg tissue weight) (p<0.05). However, there was no significant difference in serum estrogen levels between the exercise group (26.070 ± 4.064 pg/mL/100mg tissue weight) and control group (24.530 ± 8.661 pg/mL/100mg tissue weight) (p>0.05). In the Morris water maze tests, there was no difference in the spatial learning between both groups (p>0.05). The spatial memory retention of the exercise group was significantly better than control group (p<0.05). In conclusion, regular exercise increases hippocampal estrogen levels and improves spatial memory of ovariectomized rats. Keywords: exercise - hippocampus - spatial memory - estrogen - ERβ